Kepemimpinan Pendidikan Islam dalam Sejarah Pesantren Nusantara - Ilham Afif; Isnaeni Mutiara Azahra; Lu’lu Atun Naafi’ah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
As the oldest Islamic educational institutions in Indonesia, Islamic boarding schools (pesantren) play a crucial role in shaping the character, morals, and intellect of the community, thus ensuring leadership is a key factor in maintaining the institution's sustainability and development. This study aims to analyze the characteristics and development of Islamic educational leadership in the history of Islamic boarding schools in the archipelago. The method used is qualitative research with a literature study approach through the review of various books, journals, and relevant scientific sources. The results of the study indicate that Islamic boarding school leadership was initially dominated by the charismatic, religious, and exemplary leadership style of the kiai. Over time, this style has transformed into a more adaptive and professional leadership style without abandoning Islamic values, such as trustworthiness, deliberation, sincerity, and exemplary behavior. The leadership of the kiai remains a central element in the management of Islamic boarding schools and plays a role in maintaining the balance between tradition and modernization. The implications of this study indicate that the pesantren leadership model, which integrates religious, social, and managerial values, is highly relevant in facing contemporary educational challenges and supporting the sustainable development of Islamic educational institutions.